Agricultural Land Evaluation on Coastal Areas of Kebumen Regency Based on Land Degradation Levels for Biomass Production - Sisno .; Prasmadji Sulistyanto; Suwardi .; M. Nazarudin Budiono (International Conference on Coastal and Delta Areas, 2015)
The research was aimed at identifying : (1) the type and area of agricultural land in the coastal areas of Kebumen Regency; (2) the degree of land degradation and (3) the status and the causes of land degradation. The research was undertaken using a semi-detail soil survey based on the interpretation of Landsat imagery. Methods of observation and data analysis were undertaken in accordance with the government regulation of the Republic of Indonesia No. 150/ 2000 concerning land degradation control for biomass production and Minister of Environment Regulation No. 7/2006 regarding the measurement procedures for standard criteria of land degradation for biomass production. The results indicated that: (1) existing land uses consisted ofirrigated rice field (14,849.7 Ha); rain-fed rice field (2,210.3 Ha); dry land (3,189.2 Ha); garden (844.7 Ha), grasses and shrubs (446.1 Ha); settlement, bodies of water, and beaches (9,819.1 Ha); (2) the severity of land degradation was grouped as follows: very low (10,993.5 Ha); low (20,359.2 Ha); and medium 6.4 Ha; (3) land degradation status of the area was classified as slightly damaged (score < 7) with soil fraction, soil porosity, soil permeability and redox potential values as the main determining parameters of land degradation